Decoupling of static and dynamic criticality in a driven Mott insulator - Alberto de la Torre; Kyle L. Seyler; Michael Buchhold; Yuval Baum; Gufeng Zhang; Nicholas J. Laurita; John W. Harter; Liuyan Zhao; Isabelle Phinney; Xiang Chen; Stephen D. Wilson; Gang Cao; et al. (Communications Physics, 2022)
The impulsively driven antiferromagnetic Mott insulator is a model quantum many-body system predicted to realize exotic transient phenomena, however its exploration in far-from equilibrium regimes remains experimentally challenging. Here, the authors use a combination of second harmonic optical polarimetry and coherent magnon spectroscopy to investigate the ultrafast non-equilibrium dynamics of the Mott insulator Sr2IrO4 and find evidence of a far-from-equilibrium critical regime where static and dynamic critical behaviour decouple and which could be present in a number of other quantum materials.